Synaptic signals mediated by protons and acid sensing ion channels - Uchitel, Osvaldo Daniel (2019)
Extracellular pH changes may constitute significant signals for neuronal communication. During synaptic transmission, changes in pH in the synaptic cleft take place. Its role in the regulation of presynaptic Ca2+ currents through multivesicular release in ribbon-type synapses is a proven phenomenon. In recent years, protons have been recognized as neurotransmitters that participate in neuronal communication in synapses of several regions of the CNS such as amygdala, nucleus accumbens, and brainstem. Protons are released by nerve stimulation and activate postsynaptic acid-sensing ion channels (ASICs). Several types of ASIC channels are expressed in the peripheral and central nervous system. The influx of Ca2+ through some subtypes of ASICs, as a result of synaptic transmission, agrees with the participation of ASICs in synaptic plasticity. Pharmacological and genetical inhibition of ASIC1a results in alterations in learning, memory, and phenomena like fear and cocaine-seeking behavior. The recognition of endogenous molecules, such as arachidonic acid, cytokines, histamine, spermine, lactate, and neuropeptides, capable of inhibiting or potentiating ASICs suggests the existence of mechanisms of synaptic modulation that have not yet been fully identified and that could be tuned by new emerging pharmacological compounds with potential therapeutic benefits.